The Effects of Viscous Damping Modeling Methods on Seismic Performance of RC Moment Frames Using Different Nonlinear Formulations. (August 2018) - Mohammadgholibeyki, Negar; Banazadeh, Mehdi
Abstract: Nonlinear response history analysis, contributing to seismic performance assessment, is a constructive tool for evaluating buildings' behavior and damages due to the earthquake. Applying an accurate viscous damping model constitutes a crucial part in this regard. The seismic response and performance of two reinforced concrete moment frames considering various damping modeling techniques and nonlinear elements are investigated. Two basic approaches to consider nonlinearity are selected: distributed and concentrated plasticity, using force and displacement-based fiber elements and elements that contain two end springs and elastic parts to which zero and modified initial stiffness proportional damping are allocated respectively. Rayleigh damping with mass and four different stiffness matrices are applied in fiber elements. The results of Incremental Dynamic Analysis and loss estimation, considering performance-based earthquake engineering methodology, indicate that Rayleigh damping with mass and initial stiffness overestimates collapse capacity and underestimates performance parameters, while, the model with mass and tangent stiffness with updated proportionality terms shows the opposite trend. In concentrated plasticity models, the more flexible the springs, the more conservative the evaluation of building performance.